2018
DOI: 10.1103/physreve.98.022135
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization group for the φ4 theory with long-range interaction and the critical exponent η of the Ising model

Abstract: We calculate the critical exponent η of the D-dimensional Ising model from a simple truncation of the functional renormalization group flow equations for a scalar field theory with long-range interaction. Our approach relies on the smallness of the inverse range of the interaction and on the assumption that the Ginzburg momentum defining the width of the scaling regime in momentum space is larger than the scale where the renormalized interaction crosses over from long range to short range; the numerical value … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Let us also mention the following studies: O(N) models with long-range interactions [184][185][186]; fixed points with imaginary couplings [187,188]; non-polynomial perturbations to fixed points [189][190][191][192][193]; O(N) models in finite geometries and critical Casimir forces [172,194]; nonlinear sigma models [195][196][197]; the Potts model [198].…”
Section: 34mentioning
confidence: 99%
“…Let us also mention the following studies: O(N) models with long-range interactions [184][185][186]; fixed points with imaginary couplings [187,188]; non-polynomial perturbations to fixed points [189][190][191][192][193]; O(N) models in finite geometries and critical Casimir forces [172,194]; nonlinear sigma models [195][196][197]; the Potts model [198].…”
Section: 34mentioning
confidence: 99%
“…multi-critical universality classes [41], crossover phenomena [42], and stripe phases [43,44]. Further, the effect of LR generalizations of Φ 4 interactions near the PM-FM transition was studied by Goll and Kopietz [45], who observed a finite Fisher exponent in d = 3. Lattice models with LR spin interactions have also been studied by various authors [42,[46][47][48] and shown to exhibit non-universal behavior, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The spin systems with the long-range interactions have been investigated both theoretically [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16] and experimentally [17,18,19,20,21,22]. A main concern is to clarify how the criticality between the ordered and disordered phases is affected by the power of the algebraic decay [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, relying on the correspondence between the σ-and Dmediated considerations, the authors of Ref. [13] analyzed the criticality for the D = 3 (short-range) Ising model quantitatively. Experimentally, systems with variable-range interactions have been synthesized [18,19,20].…”
Section: Introductionmentioning
confidence: 99%